2001
DOI: 10.1891/0730-0832.20.5.62
|View full text |Cite
|
Sign up to set email alerts
|

Use of Methylene Blue to Treat Methemoglobinemia in Infancy

Abstract: AN ABNORMALLY INCREASED concentration of methemoglobin in the blood (methemoglobinemia) occurs whenever there is an imbalance between oxidation and reduction of heme iron. Methemoglobin is a form of hemoglobin (the oxygen-carrying pigment of the red blood cells) in which heme iron has been oxidized to the ferric state, making it unable to transport oxygen (Table 1). Normally, methemoglobin is continuously formed at a slow rate by the oxidation of heme iron to the ferric state and is then enzymatically reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Methylene blue-based aPDT is a rapidly cidal approach that tends to overcome these issues, demonstrating 4-6 log10 (10,000 -1,000,000-fold) reduction in viability of microorganisms in laboratory biofilms over 60 seconds [32]. Methylene blue (3,7-bis[Dimethylamino]-phenazathionium chloride) is a cationic heterocyclic aromatic dye commonly used for histological visualization, treatment of methemoglobinemia [33], visualization of polyps during endoscopic polypectomy, tracing lymphatic drainage during sentinel lymph node dissection [34], and visualization of GI dysplasia [35]. aPDT using methylene blue is widely used in European countries for the disinfection of fresh frozen donor plasma and red cell suspensions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue-based aPDT is a rapidly cidal approach that tends to overcome these issues, demonstrating 4-6 log10 (10,000 -1,000,000-fold) reduction in viability of microorganisms in laboratory biofilms over 60 seconds [32]. Methylene blue (3,7-bis[Dimethylamino]-phenazathionium chloride) is a cationic heterocyclic aromatic dye commonly used for histological visualization, treatment of methemoglobinemia [33], visualization of polyps during endoscopic polypectomy, tracing lymphatic drainage during sentinel lymph node dissection [34], and visualization of GI dysplasia [35]. aPDT using methylene blue is widely used in European countries for the disinfection of fresh frozen donor plasma and red cell suspensions [36].…”
Section: Discussionmentioning
confidence: 99%
“…28: 953-956; 1891). Methylene blue has been used to treat CN poisoning [50], methemoglobinemia [51], cytostatics adverse effects [52]. Methylene blue (MB) proved to be beneficial in several neurological diseases [53] where various deficiencies of the mitochondrial CI, Complex II (CII) and/or CIII were detected.…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue is a heterocyclic aromatic chemical compound that is used to treat malaria ( Dormoi et al, 2013 ), methemoglobinemia ( Zenk, 2001 ), and ifosfamide neurotoxicity ( Patel, 2006 ). Recent studies have identified its potential neuroprotective action in ischemic stroke, Parkinson’s disease ( Wen et al, 2011 ), and Alzheimer’s disease ( Congdon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%